The Son Preference Paradox: A Qualitative Study on its Influence on Family Planning Decisions in Khairahani Municipality (Shaheed Smriti Journal, 2025)
Son preference has remained a persistent socio-cultural phenomenon influencing reproductive behavior across South Asia, including Nepal. This qualitative study examined how son preference shaped family planning decisions among households in Khairahani Municipality. The study aimed to explore underlying beliefs, lived experiences, and decision-making dynamics related to fertility intentions. Data were collected through in-depth interviews with married women and key community informants, selected purposively to capture diverse socio-economic backgrounds. Thematic analysis was employed to identify recurring patterns and meanings withinparticipants’ narratives. Findings revealed that son preference significantly influenced contraceptive use, family size decisions, and birth spacing practices, often overriding economic or health-related considerations. Women reported familial pressure, gendered expectations, and perceived social security as key drivers sustaining this preference. The study concluded that son preference functioned as a paradox within modern family planning discourse, where awareness of contraceptive methods coexisted with selective fertility behavior. Addressing this issue requires culturally sensitive interventions that challenge entrenched gender norms while strengthening reproductive autonomy.